Belatacept Combined With Transient Calcineurin Inhibitor Therapy Prevents Rejection and Promotes Improved Long‐Term Renal Allograft Function. Issue 11 (3rd July 2017) - Adams, A. B.; Goldstein, J.; Garrett, C.; Zhang, R.; Patzer, R. E.; Newell, K. A.; Turgeon, N. A.; Chami, A. S.; Guasch, A.; Kirk, A. D.; Pastan, S. O.; Pearson, T. C.; et al.
Abstract : Belatacept, a T cell costimulation blocker, demonstrated superior renal function, lower cardiovascular risk, and improved graft and patient survival in renal transplant recipients. Despite the potential benefits, adoption of belatacept has been limited in part due to concerns regarding higher rates and grades of acute rejection in clinical trials. Since July 2011, we have utilized belatacept‐based immunosuppression regimens in clinical practice. In this retrospective analysis of 745 patients undergoing renal transplantation at our center, we compared patients treated with belatacept (n = 535) with a historical cohort receiving a tacrolimus‐based protocol (n = 205). Patient and graft survival were equivalent for all groups. An increased rate of acute rejection was observed in an initial cohort treated with a protocol similar to the low‐intensity regimen from the BENEFIT trial versus the historical tacrolimus group (50.5% vs. 20.5%). The addition of a transient course of tacrolimus reduced rejection rates to acceptable levels (16%). Treatment with belatacept was associated with superior estimated GFR (belatacept 63.8 mL/min vs. tacrolimus 46.2 mL/min at 4 years, p < 0.0001). There were no differences in serious infections including rates of cytomegalovirus or BK viremia. We describe the development of a costimulatory blockade‐based strategy that ultimately allows renal transplant recipients to achieve calcineurin inhibitor–free immunosuppression. Abstract : This retrospective clinical experience highlights the use of belatacept and transient tacrolimus therapy to control rejection, limit donor‐specific antibody production, and improve long‐term renal allograft function.